Melting point and microhardness of Cu2-II-IV-VI4 compounds - DAOUD, Salah; Rekab-Djabri, Hamza; Beloufa, Nabil (International Journal of Physical Research, 2022)
In the present study, we investigate the correlation between the melting point Tm and the microhardness H of some tetragonal and ortho-rhombic Cu2-II-IV-VI4 semiconducting compounds. After analyzing the experimental data of both Tm and H, we found that the melting point Tm of Cu2-II-IV-VI4 compounds correlates linearly with the microhardness H. With a coefficient of the correlation of around 0.98, the best fit was obtained using the linear model as follow: Tm = 175.54 H +792.27. The significance of the regression is given as the probability P of the null hypothesis (that there is no correlation) P < 0.0001, while the average error on the estimation of the melting point Tm was found only at around 1.54%. Our expression related Tm and H was used to predict the microhardness H of Cu2ZnSnS4 (CZTS) material. Our value (2.68 GPa) of H of CZTS deviates from the theoretical one (2.7 GPa) by only around 0.74%.